PELATIHAN AKUNTANSI TRANSAKSI KAS DAN BANK MENGGUNAKAN PROGRAM ACCURATE BAGI SISWA SMA T1, JAKARTA - Hidajat, Nastasya Cindy; Yang, Amanda; Aileen; Sanjaya, Ivan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Cash is a very important asset for everyone, especially for companies. Cash is the main resource so that expected business activities can be carried out. The introduction of computer-based accounting is very important, especially for high school students considering current technological advances. This Community Service Activity (PKM) is one manifestation of the Tri Dharma of Higher Education, to provide benefits to the community. So far, accounting learning has always been given manually, never using an accounting application. It is hoped that this activity will provide benefits for Tarsisius 1 High School students to better understand the use of accounting programs in inputting company transactions, especially cash and bank transactions. This activity was carried out for 90 minutes in two offline sessions in December 2023. The activity included presentation of material by the Untar PKM Team, then continued with practice questions and ended with a question and answer session.